2021
DOI: 10.3390/ijerph182211870
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Internet Addiction, Internet Gaming and Anxiety among Medical Students in a Malaysian Public University during COVID-19 Pandemic

Abstract: The internet has become an important medium for learning and communication during the COVID-19 pandemic, particularly for university students. Nevertheless, an increase in internet usage could predispose people to internet addiction (IA) and internet gaming (IG). Equally, there is concern that anxiety levels have increased during the pandemic. The aim of this study is to determine the prevalence of IA and IG, and their associations with anxiety among medical students during the pandemic. Data were collected du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 47 publications
(51 reference statements)
1
32
1
Order By: Relevance
“…Finally, this study revealed that lower anxiety occurred in students with a higher rate of internet addiction in subscales such as Neglect Work and Lack of Control. These findings can be explained by the fact that higher score on internet addiction may be a protective factor against anxiety in students, which was revealed in a study by Ismail et al ( 93 ). On the other hand, there are inconsistent findings ( 94 , 95 ).…”
Section: Discussionmentioning
confidence: 86%
“…Finally, this study revealed that lower anxiety occurred in students with a higher rate of internet addiction in subscales such as Neglect Work and Lack of Control. These findings can be explained by the fact that higher score on internet addiction may be a protective factor against anxiety in students, which was revealed in a study by Ismail et al ( 93 ). On the other hand, there are inconsistent findings ( 94 , 95 ).…”
Section: Discussionmentioning
confidence: 86%
“…84 With regard to adults, eight studies showed an increased risk of developing GD symptoms in association with age (i.e., being younger than 30 years), 77,79 gender (i.e., being male), 79,87 loneliness, 79,93 maladaptive self-regulation style, 79,88 high impulsivity, 79 depressive and anxiety symptoms before the COVID-19 pandemic, 79 psychological distress, 88,94 low physical activity, 79,94 being unemployed, 94 and being affected by COVID-19. 77 Another two studies reported no significant association between the prevalence of GD and anxiety 85 or being self-isolated or quarantined. 78…”
Section: Study Outcomesmentioning
confidence: 99%
“…84 Finally, regarding young and middle-aged adults, a greater risk of developing GD symptoms has been observed in individuals reporting low physical activity, 79,94 unemployed, 94 and had been affected by COVID-19. 77 Instead, two studies reported no significant association between the prevalence of GD and anxiety 85 or being self-isolated or quarantined. 78…”
Section: Principal Findingsmentioning
confidence: 99%
See 2 more Smart Citations